Study of Malaria Vector Control Efforts in Balasuna Village, Kaledupa District Wakatobi District - Taswin; Dahmar; Wahyuddin; Amiruddin, Eky Endriana; Mursiadin (International Journal of Natural and Health Sciences, 2024)
The number of malaria cases in Southeast Sulawesi, especially Wakatobi Regency is still high. This study aims to determine the description of efforts to control the Malaria Vector in Balasuna Kaledupa District, Wakatobi Regency. This type of research is analytic research with a descriptive approach. The population in this study was 418 households with a total sample of 72 households. Analysis of the data used is univariate analysis. The results showed that malaria vector control efforts in Balasuna Village, Kaledupa Subdistrict, Wakatobi Regency, were less than 43 (59.7%) of the use of Wire Nets and 29 (40.3%) respondents were sufficient, the use of anti-mosquito drugs was 42 (58.3) %) people and less than 30 (41.7%) people, the use of mosquito nets is 41 (56.9%) people and less than 31 (43.1%) people, less abating than 44 (61.1%) people and enough 28 (38.9%) people, and making 3M efforts showed that there were enough 39 (54.2%) and 33 (45.8%) less people. Suggestions are to increase community empowerment in preventing and controlling vectors by arranging a clean environment and healthy living behavior